2016
DOI: 10.7314/apjcp.2016.17.3.985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adaptive Radiotherapy on Locally Advanced Head and Neck Cancer - A Dosimetric and Volumetric Study

Abstract: Objective of the study is to evaluate volumetric and dosimetric alterations taking place during radiotherapy for locally advanced head and neck cancer (LAHNC) and to assess benefit of replanning in them. Materials and Methods: Thirty patients with LAHNC fulfilling the inclusion and exclusion criteria were enrolled in a prospective study. Planning scans were acquired both pre-treatment and after 20 fractions (mid-course) of radiotherapy. Single plan (OPLAN) based on initial CT scan was generated and executed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
0
29
1
1
Order By: Relevance
“…Compared with the mean dose delivered with standard IMRT, ART allowed a dose reduction ranging from 0.6 Gy to 4.1 Gy in all studies [11][12][13][14][15]17,31] except one, which did not find a benefit with one replanning session [3] (Table 1). Surprisingly, the parotid glands with a dose decrease without ART have a benefit of ART, which allows further reducing the mean dose by 1.4 Gy [12].…”
Section: Parotid Glandsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with the mean dose delivered with standard IMRT, ART allowed a dose reduction ranging from 0.6 Gy to 4.1 Gy in all studies [11][12][13][14][15]17,31] except one, which did not find a benefit with one replanning session [3] (Table 1). Surprisingly, the parotid glands with a dose decrease without ART have a benefit of ART, which allows further reducing the mean dose by 1.4 Gy [12].…”
Section: Parotid Glandsmentioning
confidence: 97%
“…Three studies reported that ART achieved a dosimetric benefit for the spinal cord, decreasing the spinal cord maximum dose by 0.1 Gy to 4 Gy for several fractions, ranging from one to all fractions [3,11,13]. The benefit of this dosimetric difference is unclear and may not translate into a clinical benefit.…”
Section: Spinal Cordmentioning
confidence: 99%
“…While some of the patients had 95% or 93% isodose line shifts less than 1 mm due to 1 cm uniform body contour change, some of the patients had 95% or 93% isodose line shifts more than 4 mm. This may explain the fact that although there was literature claiming the target coverage was affected by anatomical changes (e.g., weight loss), others showed that anatomical changes had minimal effect on target coverage …”
Section: Resultsmentioning
confidence: 99%
“…There is evidence showing that weight loss is correlated with body contour changes . Weight loss for H&N patients is well‐known and body contour change due to weight loss has been quantified in some studies. Yang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation